2022
DOI: 10.1002/masy.202100428
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate Biopolymer: An Efficient, Recyclable Green Catalyst for the Synthesis of Chalcone Derivatives under Mild Conditions

Abstract: One-pot chemical synthesis of highly pure chalcone under mild conditions using biocompatible Na-alginate biopolymer is reported. Several chalcone derivatives are prepared by magnetic stirring the equimolar quantities of the appropriate methyl ketone and aryl aldehyde with sodium alginate in ethanol under neutral conditions at room temperature. It is observed that in the presence of recyclable sodium alginate biocatalyst, highly pure chalcone with excellent yields in a very short time are obtained. The chalcone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In order to overcome this problem, the blending of organic and inorganic nanocomposites materials has been utilized smartly for various gas sensing applications. [19][20][21][22] It is also found that most of the transition metal oxides are n-type semiconductors and may be used for gas sensing purpose. In the present study nanocomposite of PANI with ferrous oxide (š›¼-Fe 2 O 3 ) is prepared in situ and is used for ammonia gas sensing purpose at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this problem, the blending of organic and inorganic nanocomposites materials has been utilized smartly for various gas sensing applications. [19][20][21][22] It is also found that most of the transition metal oxides are n-type semiconductors and may be used for gas sensing purpose. In the present study nanocomposite of PANI with ferrous oxide (š›¼-Fe 2 O 3 ) is prepared in situ and is used for ammonia gas sensing purpose at room temperature.…”
Section: Introductionmentioning
confidence: 99%